Peranan game edukasi kahoot! dalam menunjang pembelajaran matematika - Wiwik Sulistiyawati Sulistiyawati; Rijalush Sholikhin Sholikhin; Dian Septi Nur Afifah; Tomi Listiawan Listiawan (Universitas Pendidikan Ganesha, 2021)
Today's education requires students and teachers to be friendly with IT. Where in the learning process using applications that help the learning process and provide a pleasant effect for students. The Kahoot platform is a medium that can be used as an alternative in learning. The purpose of this paper is to explain the role of the Kahoot educational game in supporting mathematics learning, which teachers can later use as an alternative to learning so that learning is more varied, less boring and more fun. The writing of this article uses the literature study method by examining journals related to Kahoot!. The results of this study are the use of Kahoot media in mathematics learning, namely: student learning outcomes increase, accelerate understanding of material, increase student motivation and independence, increase thinking and learning skills, students have a positive attitude in learning, students are more active in learning, learning more fun and not boring, and increase interest in learning. It is recommended for teachers to use Kahoot media in mathematics learning, although not all material is presented with Kahoot. Kahoot can be used as an alternative learning media combined with learning methods.